Pelvic Pain and Apical Prolapse Surgery: A Population-Based Retrospective Cohort Study. Issue 11 (November 2020) - Borahay, Mostafa A.; Zeybek, Burak; Patel, Parin; Lin, Yu-Li; Kuo, Yong-Fang; Kilic, Gokhan S.
Abstract : Objectives: The aims of this study were to evaluate the association of preoperative pelvic pain with operative characteristics and the association of patient and operative characteristics with postoperative pain. Methods: This is a retrospective cohort study utilizing Clinformatics DataMart, a large national commercial insurance database. We collected data for patients older than 18 years who underwent apical prolapse surgery between January 2005 and December 2014. We stratified data by preoperative (prior) pain and analyzed for associations of prior and postoperative pain. Logistic regression analysis was performed using SAS software. Results: A total of 14, 440 patients met inclusion criteria and were analyzed. Patients with prior pain were more likely to have an abdominal (open or laparoscopic) approach, a concomitant hysterectomy, but less likely to have additional repairs or a mesh insertion ( P < 0.001). Postoperative pain was less with a concomitant hysterectomy, whether they had prior pain (odds ratio [OR], 0.56; 95% confidence interval [CI], 0.41–0.77) or not (OR, 0.68; 95% CI, 0.56–0.82). Additional vaginal repairs were associated with more postoperative pain for those without prior pain (OR, 1.63; 95% CI, 1.3–2.04). Age older than 45 years was associated with less pain. Length of hospital stay of more than 2 days was associated with more pain. Conclusions: Patients with prior pain were more likely to undergo an abdominal approach and have a concomitant hysterectomy. Postoperative pain was less with a concomitant hysterectomy, but more with additional vaginal repairs. There is a need to include pain as an outcome in future studies, particularly clinical trials. Abstract : Supplemental digital content is available in the text.